2021
DOI: 10.3390/atmos12091228
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Source Apportionment of Total Suspended Particulate in the Central Himalayan Region

Abstract: The present study analyzes data from total suspended particulate (TSP) samples collected during 3 years (2005–2008) at Nainital, central Himalayas, India and analyzed for carbonaceous aerosols (organic carbon (OC) and elemental carbon (EC)) and inorganic species, focusing on the assessment of primary and secondary organic carbon contributions (POC, SOC, respectively) and on source apportionment by positive matrix factorization (PMF). An average TSP concentration of 69.6 ± 51.8 µg m−3 was found, exhibiting a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 96 publications
(189 reference statements)
2
12
0
Order By: Relevance
“…dian plains [10,[56][57][58][59][60]. In contrast, the Indian Himalayan region (IHR) still lacks systematic studies focused on the characterization of aerosols [61][62][63][64][65][66][67][68][69] and source apportionment [61,70,71] using RMs.…”
Section: Methodology 21 Experimental Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…dian plains [10,[56][57][58][59][60]. In contrast, the Indian Himalayan region (IHR) still lacks systematic studies focused on the characterization of aerosols [61][62][63][64][65][66][67][68][69] and source apportionment [61,70,71] using RMs.…”
Section: Methodology 21 Experimental Sitesmentioning
confidence: 99%
“…The site is expected to be emblematic of local and regional environments for climatic change studies [37,74,75]. Additional details about the location are available in the literature [71,72,76]. E, 31.9 • N, and 1154 m above sea level (a.s.l).…”
Section: Experimental Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships were found through statistical analysis of variance and the p-value was used to calculate the statistical level of significance in terms of the correlation coefficient (R). For probability value (p) < 0.05, the value of R will be considered significant [49]. The correlation between BC and OC is determined to be 0.93, indicating that both originate from a single source, that is, the source of combustion [46].…”
Section: Relationships Between Mass Concentration Optical and Meteoro...mentioning
confidence: 99%
“…OC and EC are emitted from various sources, including fossil fuel combustion, industrial emissions, biomass burning, vehicular exhaust, and residential solid fuel use. Source apportionment studies have identified biomass burning, vehicular exhaust, mineral dust, and coal combustion as key contributors to the total aerosol mass found in the Himalayan region. Several studies have observed an increase in the contribution of total carbonaceous aerosols at specific locations in the Himalayas. ,, Furthermore, a long-term study conducted from September 2005 to March 2016 in the central Himalayas found that the concentration of BC has been increasing at a rate of 2% per year . However, research on optical properties in the Himalayan region is limited.…”
Section: Introductionmentioning
confidence: 99%